System of Creation and Functioning of Instruments of Territories Development (Part One) - Elena Sergeevna Charkina; Sergey Nikolaevich Miroshnikov (Управленческое консультирование)
In the article questions of creation and use of various instruments of state policy used for development of certain territories are considered. The federal and regional measures of support of business and improvement of business climate, characteristic of various tools, which are carried out due to providing preferences (privileges) and construction of infrastructure for increase in investment attractiveness and providing favorable conditions for conducting business activity are compared and analyzed. The conclusion about need of development of the complex system of creation and functioning of instruments of territories development including requirements to the content of justifications of expediency of use of instruments of development of territories within one or several territorial subjects of the Russian Federation, criteria for evaluation of efficiency of their functioning taking into account multiplicative effect of complex application is drawn.